2006
DOI: 10.4049/jimmunol.177.9.5779
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Deficiency of Macrophage Migration Inhibitory Factor Impairs Murine Airway Allergic Responses

Abstract: Increased levels of macrophage migration inhibitory factor (MIF) in serum, sputum, and bronchioalveolar lavage fluid (BALF) from asthmatic patients and time/dose-dependent expression of MIF in eosinophils in response to phorbol myristate acetate suggest the participation of MIF in airway inflammation. In this study, we examined inflammation in OVA-sensitized mouse lungs in wild-type and MIF-deficient mice (MIF−/−). We report increased MIF in the lung and BALF of sensitized wild-type mice. MIF−/− mice demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 28 publications
(36 reference statements)
4
29
3
Order By: Relevance
“…Consistent with this data, MIF levels were significantly lower in colonic tissue and sera in TRX-Tg mice in a mouse model of acute DSS-induced colitis [32]. Recent studies indicate that MIF plays an essential role in the pathogenesis of allergic airway inflammation [3][4][5][6]. Upon allergen sensitization and challenge, mice lacking MIF exhibit reduced AHR, tissue eosinophilia, and mucus metaplasia with concomitant decreases in levels of eotaxin and IL-13 in BALF.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Consistent with this data, MIF levels were significantly lower in colonic tissue and sera in TRX-Tg mice in a mouse model of acute DSS-induced colitis [32]. Recent studies indicate that MIF plays an essential role in the pathogenesis of allergic airway inflammation [3][4][5][6]. Upon allergen sensitization and challenge, mice lacking MIF exhibit reduced AHR, tissue eosinophilia, and mucus metaplasia with concomitant decreases in levels of eotaxin and IL-13 in BALF.…”
Section: Discussionsupporting
confidence: 72%
“…Recent studies suggest that MIF may play a key role in the pathogenesis of airway inflammation [3][4][5][6]. Therefore, we next examined the lungs of TRX-Tg and WT mice for differences in MIF expression in our model of asthma.…”
Section: Reduced Production Of Mif By Lung Epithelial Cells From Trx-mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study using a protocol of immunization with OVA and alum to induce allergic rhinitis demonstrated that MIF -/-mice have reduced eosinophil inflammation and mucus metaplasia, but develop a robust Th2 response [44]. Recent studies also revealed a critical role of MIF on AHR, mucus production and lung inflammation in a model of asthma [34,45]. In these studies, however, using slightly different protocols to induce allergic inflammation endogenous MIF was considered essential for Th2 differentiation and IgE production induced by OVA.…”
mentioning
confidence: 99%
“…It has been proposed that the mechanism responsible for the reduced splenic T cell activation observed on MIF -/-mice upon OVA immunization involves a defect on antigen presentation [34,45]. In fact, the ability to activate T cells in vitro is compromised on macrophages and mast cells but not on DC obtained from MIF -/-mice [45]. It is unclear whether these differences on activation of T cells from spleen and lymph node is related to a preferential involvement of non-DC as APC in the spleen versus DC on draining lymph nodes.…”
mentioning
confidence: 99%